Searching for fiscal decentralization constraining effect on local expenditure: case of Visegrad countries - Maličká, Lenka (Univerzita Pardubice, 2016)
Process of fiscal decentralization was stepwise run almost in all European countries without exception of Visegrad countries as countries in transition. The main goal of the fiscal decentralization is to improve the governing process, fortify the local financial autonomy and finally to increase the effectiveness of local public good provisioning. This has brought changes in the revenue side, but also in the expenditure side of local budget, which is directly connected with public good provision. But what is the real impact of decentralization processes on localities? In this paper the influence of revenue and expenditure decentralization on local government expenditure is estimated by OLS regressions for each V4 country separately and after by a panel model for all V4 countries together. Results of estimated models reveal the significant positive impact of fiscal decentralization (the type does not matter) on local expenditure which does not support the assumption about the restrictive effect of fiscal decentralization on public expenditure, also on local level.
Keywords: local government; locasl expenditure; fiscal decentralization; decentralization hypothesis; OLS model; panel model; H31; H32; H77